The effect of continuous care model on sleep quality in postmenopausal women: a randomized clinical trial study - Farzaneh Akbari; Sousan Heydarpour; Nader Salari (Sleep Science, 2022)
Introduction and Objective: Sleep disorder leads to several mental, physical, and behavioral complications. Through continuous care model, it is possible to achieve an efficient recognition of the problems of these patients and allow them to participate in solving their health issues. The effects of continuous care model on sleep quality in postmenopausal women were examined. Material and Methods: Totally, 110 postmenopausal women visiting health center in Kermanshah, Iran took part in this clinical trial. The participants were selected between May 2017 and September 2017. The participants were allocated to control and experimental groups randomly each with 55 members. The normal cares were provided to the control group, while the experimental groups took part in group consultation sessions (once every week, four session each 60-90min). Quality of sleep was examined based on Pittsburg sleep quality index before the intervention, immediately after the intervention, and a month flowing the completion of the intervention. For data analyzing, Friedman’s test, Mann-Whitney test, and chi-square test were used in SPSS. Results: A significant difference was found in the mean scores of the quality of sleep in the experimental group in three measurements occasions in the study (p=0.001). Despite lack of any significant difference before the intervention between the two groups, there was a significant decrease in the sleep quality score in the experimental group one month after the completion of the intervention compared to the control group (p<0.05). Conclusion: The continuous care model improved the sleep quality in the postmenopausal women.